2009
DOI: 10.1007/s00421-009-0998-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 4 weeks β-alanine supplementation and isokinetic training on carnosine concentrations in type I and II human skeletal muscle fibres

Abstract: Seven male students were supplemented with beta-alanine (beta-ALG) for 4 weeks (6.4 g day(-1)) and seven with a matching placebo (PLG). Subjects undertook 4 weeks of isokinetic training with the right leg (T) whilst the left leg was untrained (UT), serving as a control. Each training session consisted of 10 x 10 maximal 90 degrees extension and flexion contractions at 180 degrees /s using a Kin-Com isokinetic dynamometer, with 1 min rest between bouts. Muscle biopsies were taken from the vastus lateralis immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
1
11

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 39 publications
7
83
1
11
Order By: Relevance
“…Nevertheless, it should be mentioned that training can stimulate the responsiveness to creatine supplementation [113;114], which is not the case with carnosine loading [58].…”
Section: Beta-alanine As a Training Aidmentioning
confidence: 99%
“…Nevertheless, it should be mentioned that training can stimulate the responsiveness to creatine supplementation [113;114], which is not the case with carnosine loading [58].…”
Section: Beta-alanine As a Training Aidmentioning
confidence: 99%
“…Since beta-alanine is considered the rate limiting substrate for carnosine production in the muscle, many studies have examined the efficacy of beta-alanine supplementation to increase intramuscular carnosine levels (1,11,15,20). Hill et al (15) examined the influence of beta-alanine supplementation on skeletal muscle carnosine concentrations.…”
Section: Beta-alanine Supplementmentioning
confidence: 99%
“…In horses and camel gluteus medius muscle, the ratio in M-Carn of type I/II is 5 and 2.3 respectively [50,74]. In humans, using HPLC-based single fibre analysis the ratio is 1.3 to 2.0 [60,[71][72][73]. Muscles with a greater ratio of type II fibres have a greater M-Carn content than muscles which have the majority of type I fibres.…”
Section: Fibre Typementioning
confidence: 99%
“…The gender differences in M-Carn during puberty may be explained by the larger cross sectional area of type II fibres present in males versus females [69,70]. Type II fibres in humans have 30 -100% greater levels of M-Carn than type I fibres [71][72][73]. When the M-Carn levels of type I and II fibres were compared by Tallon et al [60], no differences were found between males and females aged 20 -35 years.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation